The Relationship Between Family-Centeredness of Service Delivery and Parental Satisfaction with Home - Milićević, Milena; Nedović, Goran (Specijalna edukacija i rehabilitacija, 2020)
This descriptive and exploratory study aimed to examine the relationship between family-centeredness of service delivery and home and community participation of children with cerebral palsy. It was hypothesized that there would be a significant association between family-centeredness of service delivery and parental satisfaction with home and community participation in the group of school-aged children with cerebral palsy. A convenience sample included 110 children with cerebral palsy, aged 7–18 years (55% males; M age = 12.7 years, SD = 3.41). The Measure of Processes of Care (MPOC-20) was used to assess the extent to which parents of children with cerebral palsy perceived health and rehabilitation services they had been receiving as being family-centred. Overall parental satisfaction with their child’s home and community participation was evaluated by The Participation and Environment Measure for Children and Youth (PEM-CY). Analyses were performed using Spearman’s rank correlation test. Only two out of 10 tested correlations reached the level of statistical significance, both in home environment. Parents who had higher overall satisfaction with their child’s current home and community participation perceived certain aspects of health and rehabilitation services as being family-centred to a greater extent (general and specific information). The fulfilment of parents’ needs by presenting them general and child-related information could have a positive effect on their satisfaction with their child’s home participation. The findings suggest insufficient representation of the concept of participation and family-centred work principles in service planning and the evaluation of outcomes of the applied programs.